The Babylonian Talmud and late antique book culture - Amsler, Monika ca. 20./21. Jh. (Cambridge University Press, 2023)
"Describes how we should imagine the intellectual and physical formation of the text in the 6th century CE. This is achieved by way of comparison with other more or less contemporary books, thereby describing the work as a product of its own time rather than as its authors aiming at what the Talmud ultimately became: the basis of orthodox Judaism"--